Development and evaluation of lafutidine solid dispersion via hot melt extrusion: Investigating drug-polymer miscibility with advanced characterisation - Ritesh Fule; Purnima Amin (Elsevier, 2014)
In current study, immediate release solid dispersion (SD) formulation of antiulcer drug lafutidine (LAFT) was developed using hot melt extrusion (HME) technique. Amphiphilic Soluplus® used as a primary solubilizing agent, with different concentrations of selected surfactants like PEG 400, Lutrol F127 (LF127), Lutrol F68 (LF68) were used to investigate their influence on formulations processing via HME. Prepared amorphous glassy solid dispersion was found to be thermodynamically and physicochemically stable. On the contrary, traces of crystalline LAFT not observed in the extrudates according to differential scanning calorimetry (DSC), X-ray diffraction (XRD), scanning electron microscopy (SEM) and Raman spectroscopy. Raman micro spectrometry had the lowest detection limit of LAFT crystals compared with XRD and DSC. Atomic Force microscopy (AFM) studies revealed drug- polymer molecular miscibility and surface interaction at micro level. 1H-COSY NMR spectroscopy confirmed miscibility and interaction between LAFT and Soluplus®, with chemical shift drifting and line broadening. MD simulation studies using computational modelling showed intermolecular interaction between molecules. Dissolution rate and solubility of LAFT was enhanced remarkably in developed SD systems. Optimized ratio of polymer and surfactants played crucial role in dissolution rate enhancement of LAFT SD. The obtained results suggested that developed LAFT has promising potential for oral delivery and might be an efficacious approach for enhancing the therapeutic potential of LAFT.